An aluminum foil coating composition for lithium ion battery current collectors, carbon-coated aluminum foil
Patent Information
- Application Number
- CN202410104511.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-25
AI Technical Summary
[0003]目前,国内外锂离子电池生产厂家所用的涂碳铝箔,均采用全覆盖涂布方式,即在涂布区域采用密涂(不漏底材)方式,用该方式制备的涂碳铝箔虽然能够提高材料与集流体的剥离强度,但由于采用密涂方式,会导致集流体电阻率较高,电池在充放电过程中温升较大,能量损失明显
[0021]本发明从铝箔涂布浆料着手,加入不溶于水的成孔剂,使涂层在干燥阶段产生均匀的微孔,实现“蜂窝状”的多孔涂碳铝箔,制备方法简单,易操作,既能增加涂碳铝箔的表面粗糙度来提高其与正极材料的剥离强度,又能降低涂碳铝箔的电阻率和增大正极材料与集流体的接触面积,从而降低电池内阻,改善电池性能。
Smart Images

Figure CN117936801B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery current collector preparation technology, specifically relating to an aluminum foil coating composition and carbon-coated aluminum foil for lithium-ion battery current collectors. Background Technology
[0002] Utilizing functional coatings to treat the surface of battery current collectors effectively enhances the electrochemical performance of lithium-ion batteries, representing a groundbreaking technological innovation. Lithium-ion batteries commonly use aluminum foil or carbon-coated aluminum foil as the positive electrode current collector. Carbon-coated aluminum foil involves uniformly and finely coating dispersed nano-conductive graphite and carbon-coated particles onto aluminum foil. It provides excellent static conductivity, collecting the micro-currents from the active material, thereby significantly reducing the contact resistance between the positive electrode material and the current collector, and improving their adhesion. This reduces the amount of binder needed, resulting in a significant improvement in the overall battery performance.
[0003] Currently, the carbon-coated aluminum foil used by domestic and foreign lithium-ion battery manufacturers adopts a full-coverage coating method, that is, a dense coating (without exposing the substrate) is used in the coating area. Although the carbon-coated aluminum foil prepared by this method can improve the peel strength between the material and the current collector, the dense coating method leads to a higher resistivity of the current collector, resulting in a larger temperature rise and significant energy loss during the charging and discharging process of the battery.
[0004] Therefore, there is an urgent need to develop a simple, low-cost carbon-coated aluminum foil that can reduce the resistivity of current collectors. Summary of the Invention
[0005] This invention provides an aluminum foil coating composition for lithium-ion battery current collectors and a carbon-coated aluminum foil.
[0006] The technical solution of the present invention is as follows:
[0007] This invention provides an aluminum foil coating composition for lithium-ion battery current collectors, the composition comprising the following raw materials in weight percentages:
[0008] Pore-forming agent 0.1%-2%, carbon-based conductive material 5%-10%, binder 2%-5%, dispersant 1%-3%, solvent 85%-90%;
[0009] The pore-forming agent is one or more of cyclopentane, azodicarbonamide, azobisisobutyronitrile, and polyether alkane;
[0010] The composition is used for coating aluminum foil for batteries.
[0011] The carbon-based conductive material of the present invention is one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0012] The carbon-based conductive material described in this invention has a particle size of 1-25 μm.
[0013] The adhesive of the present invention is an acrylic resin; the dispersant is polyvinyl alcohol or polyvinylpyrrolidone.
[0014] The solvent used in this invention is deionized water.
[0015] The present invention also provides a carbon-coated aluminum foil for lithium-ion battery current collectors, wherein the aluminum foil is coated with a coating layer, the coating layer being formed by drying the aforementioned aluminum foil coating composition for lithium-ion battery current collectors, and the coating layer having pores with a pore size of 0.5-10 μm.
[0016] The coating described in this invention has a thickness of 1-2 μm.
[0017] The carbon-coated aluminum foil for lithium-ion battery current collectors described in this invention is prepared by coating the composition onto the surface of aluminum foil and then drying it.
[0018] The coating of the present invention has a thickness of 4-5 μm.
[0019] The drying process described in this invention involves a temperature of 100-150℃ and a time of 1-2 minutes.
[0020] Beneficial effects
[0021] This invention starts with aluminum foil coating slurry, adding a water-insoluble pore-forming agent to create uniform micropores in the coating during the drying stage, thus achieving a "honeycomb" porous carbon-coated aluminum foil. The preparation method is simple and easy to operate. It can increase the surface roughness of the carbon-coated aluminum foil to improve its peel strength with the positive electrode material, and also reduce the resistivity of the carbon-coated aluminum foil and increase the contact area between the positive electrode material and the current collector, thereby reducing the internal resistance of the battery and improving battery performance. Attached Figure Description
[0022] Figure 1 The images show the appearance of different carbon-coated aluminum foils, where (a) is the carbon-coated aluminum foil for lithium-ion battery current collectors provided in Example 3, and (b) is the carbon-coated aluminum foil for lithium-ion battery current collectors provided in Comparative Example 1. Detailed Implementation
[0023] The following examples are intended to illustrate the present invention, and not to further limit the invention.
[0024] This invention provides an aluminum foil coating composition for lithium-ion battery current collectors, the composition comprising the following raw materials in weight percentages:
[0025] Pore-forming agent 0.1%-2%, carbon-based conductive material 5%-10%, binder 2%-5%, dispersant 1%-3%, solvent 85%-90%;
[0026] The pore-forming agent is one or more of cyclopentane, azodicarbonamide, azobisisobutyronitrile, and polyether alkane;
[0027] The composition is used for coating aluminum foil for batteries.
[0028] Preferably, the pore-forming agent comprises 0.4%-1%, the carbon-based conductive material comprises 6%-9%, the binder comprises 2%-3%, the dispersant comprises 1%-2%, and the solvent comprises 85%-90%.
[0029] The optimal addition amount of the pore-forming agent is 0.7%.
[0030] The composition for coating aluminum foil provided by the present invention can improve the surface roughness of carbon-coated aluminum foil, increase the contact area between the positive electrode material and the current collector, thereby improving the peel strength between the positive electrode material and the current collector, reducing the internal resistance of the battery, and improving the cycle life of the battery.
[0031] In addition, the choice of pore-forming agent enables the carbon-coated aluminum foil provided by the present invention to have advantages such as uniform pore size and small pore diameter.
[0032] To reduce the internal resistance of the battery, specifically, the carbon-based conductive material is one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0033] In addition, the adhesive is acrylic resin; the dispersant is polyvinyl alcohol or polyvinylpyrrolidone.
[0034] The raw materials used in this invention include carbon-based conductive materials, which are mainly used to reduce battery internal resistance and improve capacity evaporation; binders, which provide a stable supporting effect for the system; and dispersants, which are mainly used to improve the dispersibility of the conductive paste and ensure good wetting and flowability of the composition during coating. This invention achieves the effect of reducing battery internal resistance through the synergistic effect of the various raw materials.
[0035] Considering that both particle size uniformity and particle size affect the electrochemical performance of the electrode, the carbon-based conductive material preferably has a particle size of 1-25 μm. The stirring process avoids the generation of large particles, which could prevent the formation of good conductive channels later.
[0036] Preferably, the solvent is deionized water. This not only improves the solubility of each raw material in the solvent, ensuring the dispersibility and stability of the composition, but also satisfies the compatibility of the pore-forming agent in the composition, thereby ensuring that the coating produces uniform micropores during the drying stage.
[0037] This invention also provides a carbon-coated aluminum foil for lithium-ion battery current collectors. The aluminum foil is coated with a layer containing pores with a pore size of 0.5-10 μm. The coating is formed by drying the aforementioned aluminum foil coating composition for lithium-ion battery current collectors. This operation is simple and easy to control, and the raw materials are readily available.
[0038] To ensure battery performance, the coating thickness is further controlled, and the coating thickness is 1-2 μm.
[0039] Specifically, the carbon-coated aluminum foil for lithium-ion battery current collectors is prepared by coating the composition onto the surface of aluminum foil and then drying it.
[0040] This invention starts with aluminum foil coating slurry, adding a water-insoluble pore-forming agent to create uniform micropores in the coating during the drying stage, resulting in a "honeycomb" porous carbon-coated aluminum foil. The preparation method is simple and easy to operate. It can increase the surface roughness of the carbon-coated aluminum foil to improve its peel strength with the positive electrode material, and also reduce the resistivity of the carbon-coated aluminum foil and increase the contact area between the positive electrode material and the current collector, thereby reducing the internal resistance of the battery and improving battery performance.
[0041] To further ensure dispersibility, the composition needs to be stirred evenly before coating. The stirring speed is 1000-1500 rpm, the time is 45-60 min, and the temperature is 24-26℃. The stirred slurry is then dispersed by a grinder at a speed of 800-1500 rpm for 60-240 min at a temperature of 20-45℃. Under mechanical shear force, the particle agglomerates are fully deagglomerated and dispersed.
[0042] In addition, considering that the pore-forming agent will volatilize during the subsequent drying process, the coating thickness needs to be controlled. The coating thickness is 4-5 μm.
[0043] After coating the composition onto the surface of aluminum foil, drying is performed by utilizing the vaporization property of the pore-forming agent upon heating. The drying process takes place at a temperature of 100-150℃ for 1-2 minutes. After drying and cooling to room temperature, a honeycomb-like porous carbon-coated aluminum foil is obtained, with a coating thickness of 1-2 μm.
[0044] In the following examples, deionized water was used as the solvent, the particle size of the carbon-based conductive material was 1-25 μm, the binder was acrylic resin, the resulting carbon-coated aluminum foil had a coating thickness of 1-2 μm, and the pore size of the pores distributed in the coating was 0.5-10 μm.
[0045] Example 1
[0046] A pore-forming agent, cyclopentane, was added to carbon-based conductive graphite, a binder, a dispersant, polyvinyl alcohol, and deionized water. The mixture was stirred at 24°C and 1000 rpm for 60 minutes. The resulting slurry was then dispersed in a grinder at 800 rpm for 240 minutes at 20°C until homogeneous, yielding a composition. This composition was coated onto an aluminum foil surface to a thickness of 4-5 μm and dried at 110°C for 2 minutes. The resulting coating had a thickness of 1 μm, with pores of 0.5-1 μm in diameter. The composition, by mass percentage, consisted of 0.1% cyclopentane, 10% carbon-based conductive graphite, 2.5% binder, 1.5% dispersant, and 85.9% deionized water.
[0047] Example 2
[0048] A pore-forming agent, cyclopentane, was added to carbon-based conductive material (conductive carbon black), a binder, a dispersant (polyvinyl alcohol), and deionized water. The mixture was stirred at 26°C and 1500 rpm for 45 minutes. The resulting slurry was then dispersed in a grinder at 1000 rpm for 200 minutes at 30°C until homogeneous, yielding a composition. This composition was coated onto an aluminum foil surface to a thickness of 4-5 μm and dried at 130°C for 1 minute. The resulting coating had a thickness of 1.2 μm, with pores of 0.5-3 μm in diameter. The composition, by mass percentage, consisted of 0.4% cyclopentane, 6.6% carbon-based conductive material (conductive carbon black), 2% binder, 1% dispersant, and 90% deionized water.
[0049] Example 3
[0050] A pore-forming agent, cyclopentane, was added to carbon-based conductive material (conductive carbon black), a binder, a dispersant (polyvinyl alcohol), and deionized water. The mixture was stirred for 60 minutes at 25°C and 1000 rpm. The resulting slurry was then dispersed in a grinder at 1200 rpm for 150 minutes at 35°C until homogeneous, yielding a composition. This composition was then coated onto an aluminum foil surface to a thickness of 4-5 μm and dried at 120°C for 2 minutes. The resulting coating had a thickness of 1.4 μm, with pores of 1-5 μm in diameter. The composition, by mass percentage, consisted of 0.7% cyclopentane, 9% carbon-based conductive material (conductive carbon black), 2% binder, 1% dispersant, and 87.3% deionized water.
[0051] Example 4
[0052] A pore-forming agent, cyclopentane, was added to carbon nanotubes (a carbon-based conductive material), a binder, a dispersant, polyvinylpyrrolidone, and deionized water. The mixture was stirred at 25°C and 1200 rpm for 50 minutes. The resulting slurry was then dispersed in a grinder at 1300 rpm for 100 minutes at 40°C until homogeneous, yielding a composition. This composition was then coated onto an aluminum foil surface to a thickness of 4-5 μm and dried at 100°C for 2 minutes. The resulting coating had a thickness of 1.6 μm, with pores having a diameter of 1.7-7 μm. The composition, by mass percentage, consisted of 1% cyclopentane, 5% carbon nanotubes, 3% binder, 2% dispersant, and 89% deionized water.
[0053] Example 5
[0054] A pore-forming agent, cyclopentane, was added to graphene (a carbon-based conductive material), a binder, polyvinylpyrrolidone (a dispersant), and deionized water. The mixture was stirred for 50 minutes at 25°C and 1200 rpm. The resulting slurry was then dispersed in a grinder at 1500 rpm for 60 minutes at 45°C until homogeneous, yielding a composition. This composition was then coated onto an aluminum foil surface to a thickness of 4-5 μm and dried at 140°C for 1 minute. The resulting coating had a thickness of 1.8 μm, with pores of 2.7-10 μm in diameter. The composition, by mass percentage, consisted of 1.5% cyclopentane, 6% graphene, 5% binder, 1% dispersant, and 86.5% deionized water.
[0055] Example 6
[0056] A pore-forming agent, cyclopentane, was added to carbon-based conductive material (conductive carbon black), a binder, a dispersant (polyvinylpyrrolidone), and deionized water. The mixture was stirred for 60 minutes at 25°C and 12000 rpm. The resulting slurry was then dispersed in a grinder at 800 rpm for 240 minutes at 20°C until homogeneous, yielding a composition. This composition was coated onto an aluminum foil surface to a thickness of 4-5 μm and dried at 150°C for 1 minute. The resulting coating had a thickness of 2 μm, with pores of 4-10 μm in diameter. The composition, by mass percentage, consisted of 2% cyclopentane, 8% carbon-based conductive material (conductive carbon black), 2% binder, 3% dispersant, and 85% deionized water.
[0057] Example 7
[0058] Compared to Example 3, the pore-forming agent added was azodicarbonamide. All other operations were the same as in Example 3.
[0059] Example 8
[0060] Compared to Example 3, the pore-forming agent added was azobisisobutyronitrile. All other operations were the same as in Example 3.
[0061] Example 9
[0062] Compared to Example 3, the added pore-forming agent is a polyether alkane. The remaining operations are the same as in Example 3.
[0063] Comparative Example 1
[0064] Compared to Example 3, no pore-forming agent was added; instead, the composition was directly coated onto the surface of aluminum foil and dried. The remaining operations were the same as in Example 3, with the same raw materials and amounts added.
[0065] Comparative Example 2
[0066] Compared to Example 3, the added pore-forming agent was sodium bicarbonate. The remaining operations were the same as in Example 3, with the same raw materials and amounts added.
[0067] Comparative Example 3
[0068] Compared to Example 3, the amount of pore-forming agent cyclopentane added was 4% of the composition. The remaining operations were the same as in Example 3, with the same raw materials and amounts added as in Example 3.
[0069] Performance testing experiment
[0070] The appearance morphology of the carbon-coated aluminum foils for lithium-ion battery current collectors prepared in Examples 3 and 1 (Comparative Example 1) was inspected. Additionally, the carbon-coated aluminum foils for lithium-ion battery current collectors prepared in Examples 1-9 and 1-3 were coated with lithium iron phosphate as the positive electrode material, dried, and then used to obtain positive electrode sheets. The peel strength and electrode resistance of the positive electrode sheets were tested. The peel strength was tested using a tensile testing machine according to the method shown in GB2792-2014 and converted to N / m. The electrode resistance was tested using the four-probe method to measure the surface contact resistance of the carbon-coated aluminum foil coating. The results are as follows:
[0071] 1. Appearance and morphology
[0072] Figure 1 The carbon-coated aluminum foils for lithium-ion battery current collectors prepared in Example 3(a) and Comparative Example 1(b) were observed at a magnification of 300x to obtain their surface morphology. It can be seen that, compared to Comparative Example 1, the carbon-coated aluminum foil for lithium-ion battery current collectors prepared in Example 3(a) has a distinctly porous "honeycomb" arrangement on its surface, thereby increasing the surface roughness and surface area.
[0073] 2. Peel strength
[0074] Table 1 Comparison of peel strength of different carbon-coated aluminum foils
[0075]
[0076] As shown in Table 1, the peel strength in Examples 1-9 is significantly improved compared with Comparative Examples 1-3, indicating that the carbon-coated aluminum foil prepared using the aluminum foil coating composition for lithium-ion battery current collectors provided in this application increases the contact area between the coating and the positive electrode material, thereby improving the peel strength between the carbon-coated aluminum foil and the positive electrode material.
[0077] 3. Electrode Resistors
[0078] Table 2 Comparison of electrode resistances with different carbon-coated aluminum foils
[0079]
[0080]
[0081] As shown in Table 2, compared with Comparative Examples 1-3, the electrode resistance in Examples 1-9 is significantly reduced, indicating that the carbon-coated aluminum foil prepared using the aluminum foil coating composition for lithium-ion battery current collectors provided in this application reduces the battery internal resistance and thus improves the battery cycle life.
Claims
1. An aluminum foil coating composition for lithium-ion battery current collectors, characterized in that, The composition comprises the following raw materials in weight percentages: Pore-forming agent 0.1%-2%, carbon-based conductive material 5%-10%, binder 2%-5%, dispersant 1%-3%, solvent 85%-90%; The pore-forming agent is one or more of cyclopentane, azodicarbonamide, azobisisobutyronitrile, and polyether alkane; The solvent is deionized water; The composition is used for coating aluminum foil for batteries.
2. The aluminum foil coating composition for lithium-ion battery current collectors according to claim 1, characterized in that, The carbon-based conductive material is one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
3. The aluminum foil coating composition for lithium-ion battery current collectors according to claim 1, characterized in that, The carbon-based conductive material has a particle size of 1-25 μm.
4. The aluminum foil coating composition for lithium-ion battery current collectors according to claim 1, characterized in that, The adhesive is acrylic resin; the dispersant is polyvinyl alcohol or polyvinylpyrrolidone.
5. A carbon-coated aluminum foil for use as a current collector in lithium-ion batteries, characterized in that, The aluminum foil is coated with a coating, which is formed by drying the aluminum foil coating composition for lithium-ion battery current collectors according to any one of claims 1-4, and the coating contains pores with a pore size of 0.5-10 μm.
6. The carbon-coated aluminum foil for lithium-ion battery current collectors according to claim 5, characterized in that, The coating has a thickness of 1-2 μm.
7. The carbon-coated aluminum foil for lithium-ion battery current collectors according to claim 5, characterized in that, The composition is prepared by coating the surface of aluminum foil and then drying it.
8. The carbon-coated aluminum foil for lithium-ion battery current collectors according to claim 7, characterized in that, The coating has a thickness of 4-5 μm.
9. The carbon-coated aluminum foil for lithium-ion battery current collectors according to claim 7, characterized in that, The drying process is carried out at a temperature of 100-150℃ for 1-2 minutes.
Citation Information
Patent Citations
Safety liquid and preparation method thereof, as well as material with safety coating and application of material
CN112701244A
Carbon-coated aluminum foil for lithium ion battery and preparation method of carbon-coated aluminum foil
CN117423837A
